2019
DOI: 10.1042/bsr20181847
|View full text |Cite
|
Sign up to set email alerts
|

The effects of novel α2-adrenoreceptor agonist dexmedetomidine on shivering in patients underwent caesarean section

Abstract: Objective: Meperidine used to control shivering during perioperative period has associated side effects. The present study compared the safety of selective α2-adrenoreceptor agonist dexmedetomidine and meperidine for anti-shivering in primiparas after caesarean delivery under combined spinal-epidural anesthesia (CSEA).Methods: 100 primiparas scheduled for caesarean delivery were randomly allocated to dexmedetomidine group (Group D, n=50) and meperidine positive control group (Group M, n=50). Primiparas experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Yu et al. 9 suggested that dexmedetomidine 0.05 μg/kg/hour is a better choice for anti-shivering, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Yu et al. 9 suggested that dexmedetomidine 0.05 μg/kg/hour is a better choice for anti-shivering, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of spinal anesthesia, the possibility of shivering during cesarean section is 55%.3 Intraoperative shivering leads to increased oxygen consumption and carbon dioxide production, which has a certain impact on maternal physiological functions.21 The cause of shivering during cesarean section under spinal anesthesia is still unknown, but the occurrence of shivering may be related to the loss of heat, the suppression of the body’s thermoregulatory mechanism, and the redistribution of heat in the body. Dexmedetomidine may play an antishivering role by regulating the shivering threshold of the central thermoregulatory system and reducing the contraction of vessels 12,22. Although intravenous dexmedetomidine can reduce the incidence of shivering, it has an inhibitory effect on the respiratory rate.23 Intrathecal dexmedetomidine inhibits the body’s thermoregulatory center by inhibiting the transmission of body temperature information at the level of the spinal cord, ultimately reducing the incidence of shivering during cesarean section.2 Our meta-analysis found that intrathecal dexmedetomidine significantly reduces the incidence of shivering during cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can be administered intravenously or intrathecally during spinal anesthesia, but there is some controversy about which method should be used during anesthesia for pregnant women. The use of dexmedetomidine by the intravenous route has been reported to result in hemodynamic instability.12 Therefore, we aimed to investigate the effect of intrathecal dexmedetomidine on the adverse effects of spinal anesthesia during cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…α 2 -Adrenergic agonists cause myometrial contraction by inducing an influx of extracellular Ca 2+ , probably through VDCCs and the release of arachidonic acid [22]. Several recent studies reported that dexmedetomidine is effective for treating postpartum shivering in cesarean sections [23][24][25] and can improve early breastfeeding outcomes [26]. α 2 -Adrenoceptor activation reportedly results in the release of arachidonic acid in vascular smooth muscle [27].…”
Section: Introductionmentioning
confidence: 99%